2006
DOI: 10.1111/j.1600-6143.2006.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of the Cold Preserved Rat Liver by Hypothermic Oxygenated Machine Perfusion

Abstract: The aim of the study was to investigate whether hypothermic oxygenated liver perfusion after cold liver preservation resuscitated metabolic parameters and whether this treatment had a benefit for liver viability upon reperfusion.We preserved rat livers either by cold storage (UW) for 10 h, or by perfusion for 3 h (oxygenated modified UW) after 10 h cold storage. We assessed viability of livers after preservation and after ischemic rewarming + normothermic reperfusion ex vivo. Ten hour cold storage reduced mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 43 publications
7
92
0
1
Order By: Relevance
“…As expected from previous studies, 6,8 HOPE reduced reperfusion injury within the first 24 hours after OLT, confirmed by minimal 8-OHdG, HMGB-1, and AST release and decreased activation of Kupffer and endothelial cells (Figs 1, 2). Furthermore, HOPE treatment prevented infiltration of CD3-positive T cells in liver grafts (Fig.…”
Section: Liver Graft Protection By Short-term Application Of Hope Witsupporting
confidence: 89%
See 2 more Smart Citations
“…As expected from previous studies, 6,8 HOPE reduced reperfusion injury within the first 24 hours after OLT, confirmed by minimal 8-OHdG, HMGB-1, and AST release and decreased activation of Kupffer and endothelial cells (Figs 1, 2). Furthermore, HOPE treatment prevented infiltration of CD3-positive T cells in liver grafts (Fig.…”
Section: Liver Graft Protection By Short-term Application Of Hope Witsupporting
confidence: 89%
“…5 The perfusion technique consisted of a short-term hypothermic oxygenated perfusion (HOPE) after conventional organ procurement and cold storage and was shown to protect effectively from ischemia-reperfusion (I/R) injury despite long donor warm ischemia times. [6][7][8] We have also reported, in several experimental studies, that such effects of HOPE depend on oxygenation of the perfusate 6 with decreased downstream activation of numerous inflammatory pathways. 6,7 On the basis of these findings, the aim of the current study was to analyze effects of HOPE treatment on the immune response in a model of acute rejection, using incompatible rat strains for OLT.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The hypothermic perfusion setting, however, fundamentally differs from normothermic physiological conditions. During cold machine liver perfusion, oxygen consumption of any liver cells, including the extrahepatic bile duct, is dramatically reduced, and we convincingly reported that single portal vein perfusion with high oxygen tension enables sufficient liver ATP reload in the cold before graft implantation (6)(7)(8).To support our observation, recent human application of single portal vein HOPE in extended DCD livers displayed a significant reduction of biliary complications with robust graft survival benefit, compared to matched unperfused DCD livers (9).…”
Section: ) (5)supporting
confidence: 68%
“…In the last decade, experimental studies have shown that continuous perfusion of the liver during preservation can improve graft viability and challenge the limits of the current static storage. 8,9 However, the mode of oxygen supply remains unclear. Optimization of oxygen delivery during hypothermic preservation is essential.…”
Section: Introductionmentioning
confidence: 99%